Hubungan Budaya dan Pengetahuan Dengan Kejadian Kekurangan Energi Kronik Pada Ibu Hamil Trimester I di Daerah Pesisir - Lilik Firdausi; Eko Mulyadi (SAKTI BIDADARI (Satuan Bakti Bidan Untuk Negeri), 2022)
Things that need to be considered in studying eating habits are food consumption (quantity and quality), preferences for certain foods, beliefs, taboos, or attitudes towards certain foods. Lack of knowledge of pregnant women about nutrition affects the behavior of mothers in terms of food selection in fulfilling nutrition, thus causing a lack of nutritious food during pregnancy which can cause Chronic Energy Lack (CEL) in pregnancy. The Chronic Energy Lack (CEL) caused by lack insufficient energy and protein were to pregnant women. Chronic Energy Lack (CEL) for pregnant women were arm circumference above <23.5 cm and low birth weight babies (LBW) able to the potential to die, growth disorders and child development disordes. Also it was an indirect cause of maternal death. The purpose of this study was to determine the relationship between culture and knowledge with the incidence of Chronic Energy Lack (CEL) in first trimester pregnant women in coastal areas. The type of research is analytic observational with a cross sectional design to 49 respondents by purposive sampling, the subject is pregnant women who meet the inclusion and exclusion criteria by using a questionnaire. analysis using Chi-Square Test, from 49 respondents it is known that pregnant women who have good knowledge are 61.2%, pregnant women who have culture in the supportive category are 73,5% The results of the ChiSquare analysis test obtained a p value of 0.046 <0.05 which means that there is a significant relationship between the relationship between knowledge and Chronic Energy Lack (CEL) in Bunder Village, Pesisir District, Pademawu District, Pamekasan Regency.